THE RELATIONSHIP BETWEEN BIOLOGY LEARNING EXPERIENCES ABOUT STUNTING ISSUES AND THE SCIENCE LITERACY ABILITIES OF GRADE XI MIPA STUDENTS OF MAN 2 YOGYAKARTA - Aryadi, Amanda Sefhia; Kurniawati, Atik (Jurnal Edukasi Biologi, 2025)
This research was conducted at MAN 2 Yogyakarta and involved 65 students from grade XI MIPA, who were selected as samples using the census method. This type of research is correlational ex post facto with a quantitative approach. Biology learning experiences were measured using a Likert scale questionnaire and supported by in-depth interviews with teachers, while students' scientific literacy abilities were assessed using a test created in reference to the PISA 2018 competency aspects. Data analysis techniques used descriptive analysis and Pearson Product-Moment correlation analysis. The results showed that students' biology learning experiences that were categorised as very high were four students (6%), high were 15 students (23%), moderate were 29 students (45%), low were 13 students (20%), and very low were four students (6%). Scientific literacy abilities on the issue of stunting that were categorised as very high were three students (5%), high were 22 students (34%), moderate were 24 students (37%), low were 12 students (18%), and very low were four students (6%). There is a positive and significant relationship between biology learning experiences and stunting issues, as well as scientific literacy skills (correlation coefficient of 0.283 and significance of 0.022). Furthermore, biology learning experiences are known to have only an 8% influence on scientific literacy skills, with 92% being influenced by other factors, such as the selection of teaching materials and the use of learning media. Based on the research results, it can be concluded that the better the biology learning experience, the better the students' scientific literacy skills on stunting issues.